A bear’s biography: hybrid warfare and the more-than-human battlespace - Forsyth, Isla (Sage, 2016)
This paper makes an intervention highlighting the animal dimension of military geographies as an overlooked yet illuminating aspect of the hybrid nature of warfare. By bringing animal geographies into dialogue with critical military geographies and with a focus on relational ethics, the processes, performance and consequences of the more-than-human nature of the battlespace are examined through a vignette of Wojtek the bear. Wojtek was a mascot, pet and officially enlisted soldier of the Polish Army in the Second World War who travelled the desert plains, helped to fight at the Battle of Monte Cassino, before being demobbed with his fellow Polish comrades in the UK, eventually ending his civilian days in Edinburgh Zoo. Although a well-known figure Wojtek and his biography have predominately been used as a means to explore the Polish soldiers’ experience of the Second World War with the result that the bear as an animal is absent. This paper, therefore, puts the bear back into his biography in order to acknowledge the role and lived experience of animals in the military. Further, it suggests that exploring the place of animals in the military requires geographers to articulate the hybrid nature of warfare and also to explore the ethico-political relations this produces.